Comparison between esomeprazole 20 mg Vs 40 mg as stress ulcer prophylaxis (SUP) in critically ill patients: A retrospective cohort study - Khalid Al Sulaiman; Kholoud Al Aamer; Alaa Al Harthi; Saud Jaser; Abdulrahman Al Anazi; Sultan Al Subaie; Ramesh Vishwakarma (Wiley, 2020)
Abstract Critically ill patients admitted to intensive care units (ICUs) are at high risk of developing upper gastrointestinal bleeding due to GI stress ulceration (SU). The major independent risk factors for the development of GI bleeding in the ICUs include mechanical ventilation (MV) and coagulopathy. There is no enough evidence regarding the most appropriate dosing of esomeprazole as stress ulcer prophylaxis (SUP) in critically ill patients. This is a retrospective cohort study conducted at King Abdulaziz Medical City‐Riyadh between January and December 2018 to determine the efficacy and safety of two different regimens of esomeprazole (20 vs 40 mg) as SUP in critically ill patients with major risk factors of GI stress ulceration. A total of 1864 patients were reviewed, 387 patients meeting inclusion criteria were enrolled. The propensity score was used to adjust for clinically and statistically relevant variables. We considered a P value of <.05 as statistically significant. 49 patients (12.6%) had received Esomeprazole 20 mg during the study period. Compared with Esomeprazole 20 mg, Esomeprazole 40 mg was not superior in GI bleeding prevention (aOR 2.611, 95% CI 0.343‐20.247, P = .356). In addition, neither ICU C. difficle, ICU mortality within 30 days, ICU LOS, hospital LOS, ICU re‐admission within 6 months, RBCs transfusion, nor platelets transfusion requirements were significant. On the other hand, Esomeprazole 40 mg was statistically associated with Enterobacteriaceae, Pneumonia, and longer MV duration.